2009
DOI: 10.1097/tp.0b013e318199d19a
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Urogenital Mycoplasmas and Ureaplasmas in Women After Kidney Transplantation

Abstract: Our observation showed the necessity of careful examination of possible atypical pathogens in diagnostic materials from hemodialyzed and kidney transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…One such population of immunocompromised individuals is solid organ transplant recipients. Ekiel et al found increased Ureaplasma and Mycoplasma urogenital colonization of kidney transplant and dialysis patients compared with age‐matched controls. They found a fourfold increase in U urealyticum colonization among transplanted and dialysis patients as well as a 50% increase in any Mycoplasmatale.…”
Section: Discussionmentioning
confidence: 96%
“…One such population of immunocompromised individuals is solid organ transplant recipients. Ekiel et al found increased Ureaplasma and Mycoplasma urogenital colonization of kidney transplant and dialysis patients compared with age‐matched controls. They found a fourfold increase in U urealyticum colonization among transplanted and dialysis patients as well as a 50% increase in any Mycoplasmatale.…”
Section: Discussionmentioning
confidence: 96%
“…Ekiel et al reported a higher frequency of urogenital colonization with U. urealyticum in young asymptomatic female kidney allograft recipients or dialysis patients (10%) as compared to matched healthy individuals (2.5%), whereas other Mycoplasma spp. with a less pathogenic potential are found equally often.…”
Section: Discussionmentioning
confidence: 99%
“…Although coinfections were common, multiple logistic regression revealed that only MG colonization was significantly associated with cervicitis [6]. Among nonpregnant women, MG also has been associated with salpingitis and in a study of Cefoxitin treatment of salpingitis, failure to eliminate symptoms was attributed to eradicate MG [7]. And in a study of Swedish women undergoing elective termination, postabortal salpingitis was associated with MG colonization in 2.8% of women, furnishing an odds ratio above 6-fold compared to noncolonized women [8].…”
Section: Mycoplasma Genitalium (Mg)mentioning
confidence: 99%